Changes in land use and management led to a decline in Eastern Europe’s terrestrial carbon sink - Winkler, Karina; Yang, Hui; Ganzenmüller, Raphael; Fuchs, Richard; Ceccherini, Guido; Duveiller, Grégory; Grassi, Giacomo; Pongratz, Julia; Bastos, Ana; Shvidenko, Anatoly; Araza, Arnan; Herold, Martin; et al. (Communications earth & environment, 2023)
Land-based mitigation is essential in reducing net carbon emissions. Yet, the attribution of carbon fluxes remains highly uncertain, in particular for the forest-rich region of Eastern Europe (incl. Western Russia). Here we integrate various data sources to show that Eastern Europe accounted for an above-ground biomass carbon sink of ~0.41 gigatons of carbon per year over the period 2010–2019, that is 78% of the entire European carbon sink. We find that this carbon sink is declining, mainly driven by changes in land use and land management, but also by increasing natural disturbances. Based on a random forest model, we show that land use and management changes are main drivers of the declining carbon sink in Eastern Europe, although soil moisture variability is also important. Specifically, the saturation effect of tree regrowth in abandoned agricultural areas, combined with increasing wood harvest removals, particularly in European Russia, contributed to the decrease in the Eastern European carbon sink.